2023
DOI: 10.3390/plants12030518
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights on Salicylic Acid Mediated Enhancement of Photosystem II Function in Oregano Seedlings Subjected to Moderate Drought Stress

Abstract: Dramatic climate change has led to an increase in the intensity and frequency of drought episodes and, together with the high light conditions of the Mediterranean area, detrimentally influences crop production. Salicylic acid (SA) has been shown to supress phototoxicity, offering photosystem II (PSII) photoprotection. In the current study, we attempted to reveal the mechanism by which SA is improving PSII efficiency in oregano seedlings under moderate drought stress (MoDS). Foliar application of SA decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 123 publications
0
28
0
Order By: Relevance
“…Mainly, the maximal quantum yield of PSII (F v /F m ) and the electron transport outside Q A − (F v /F 0 ) are used as important reliable indicators reflecting the performance of PSII under an unfavorable environment [24]. Under drought stress conditions, an overexcitation of PSII occurs, because the absorbed light energy exceeds the capabilities of the chloroplasts to utilize it, which in turn causes further photoinhibition and photodamage, as indicated by decreased maximal quantum yield of PSII (F v /F m ) [25,26]. PSII photodamage can happen through photooxidative stress, either at the acceptor side or at the donor side via inactivation of the oxygen-evolving complex [27,28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mainly, the maximal quantum yield of PSII (F v /F m ) and the electron transport outside Q A − (F v /F 0 ) are used as important reliable indicators reflecting the performance of PSII under an unfavorable environment [24]. Under drought stress conditions, an overexcitation of PSII occurs, because the absorbed light energy exceeds the capabilities of the chloroplasts to utilize it, which in turn causes further photoinhibition and photodamage, as indicated by decreased maximal quantum yield of PSII (F v /F m ) [25,26]. PSII photodamage can happen through photooxidative stress, either at the acceptor side or at the donor side via inactivation of the oxygen-evolving complex [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…PSII photodamage can happen through photooxidative stress, either at the acceptor side or at the donor side via inactivation of the oxygen-evolving complex [27,28]. Under drought stress conditions, the availability of water for oxidation is limited, which reduces the efficiency of the oxygen-evolving complex at the donor side (F v /F 0 ) [25,29]. Our results indicate that additional oxidative damage could take place because of limited photoprotection as a consequence of decreased carotenoids content in drought-treated plants (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Exogenously applied SA in oregano seedlings has been reported to enhance PSII functionality under NS conditions only under HL and not under low light (LL) [ 79 ]. However, under mild drought stress (MiDS), it improved PSII photochemistry at both LL and HL conditions [ 79 ].…”
Section: Introductionmentioning
confidence: 99%
“…Exogenously applied SA in oregano seedlings has been reported to enhance PSII functionality under NS conditions only under HL and not under low light (LL) [ 79 ]. However, under mild drought stress (MiDS), it improved PSII photochemistry at both LL and HL conditions [ 79 ]. Since it has been suggested that the mode of action of SA varies with plant species [ 50 , 56 , 79 ], we evaluated the responses of basil plants to exogenously applied SA under the same experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Global climate change has quickly turned into a huge issue in the agricultural industry due to increased episodes of drought and elevated temperature that, together with the longer sunlight hours of the Mediterranean area, detrimentally influence crop production [ 1 , 2 , 3 , 4 ]. For example, leguminous lentil in the Mediterranean region is affected by huge fluctuations in seasonal precipitation, with intensive rainfalls in winter, and drought and high-temperature stress from March to May [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%